The Wordwall-Based Gamification in Teaching English Vocabulary - Febrianti, Dina Triana; Taufiq, Wahyu (Universitas Siliwangi, 2025)
This study explores the effect of Wordwall-based gamification strategy in improving English vocabulary mastery among Junior High School students. This study uses a quantitative approach with a one-group pretest-posttest experimental design. Participants consisted of 22 seventh grade students selected based on their low English learning outcomes. Data were collected through vocabulary tests given before and after the intervention. Statistical analysis, using normality tests, descriptive statistics and paired sample t-tests. The results of this study indicate that learning with Wordwall media gamification strategy can significantly improve students' English vocabulary (sig. (2-tailed) 0.00 0.05) which indicates an increase in English vocabulary mastery after the intervention. It is concluded that the use of Wordwall is effective in improving students' vocabulary.